Brain Injury Is More Common in Venoarterial Extracorporeal Membrane Oxygenation Than Venovenous Extracorporeal Membrane Oxygenation: A Systematic Review and Meta-Analysis. Issue 12 (December 2020) - Shoskes, Aaron; Migdady, Ibrahim; Rice, Cory; Hassett, Catherine; Deshpande, Abhishek; Price, Carrie; Hernandez, Adrian V.; Cho, Sung-Min
Abstract : Objectives: Despite the common occurrence of brain injury in patients undergoing extracorporeal membrane oxygenation, it is unclear which cannulation method carries a higher risk of brain injury. We compared the prevalence of brain injury between patients undergoing venoarterial and venovenous extracorporeal membrane oxygenation. Data Sources: PubMed and six other databases from inception to April 2020. Study Selection: Observational studies and randomized clinical trials in adult patients undergoing venoarterial extracorporeal membrane oxygenation or venovenous extracorporeal membrane oxygenation reporting brain injury. Data Extraction: Two independent reviewers extracted the data from the studies. Random-effects meta-analyses were used to pool data. Data Synthesis: Seventy-three studies ( n = 16, 063) met inclusion criteria encompassing 8, 211 patients (51.2%) undergoing venoarterial extracorporeal membrane oxygenation and 7, 842 (48.8%) undergoing venovenous extracorporeal membrane oxygenation. Venoarterial extracorporeal membrane oxygenation patients had more overall brain injury compared with venovenous extracorporeal membrane oxygenation (19% vs 10%; p = 0.002). Venoarterial extracorporeal membrane oxygenation patients had more ischemic stroke (10% vs 1%; p < 0.001), hypoxic-ischemic brain injury (13% vs 1%; p < 0.001), and brain death (11% vs 1%; p = 0.001). In contrast, rates of intracerebral hemorrhage (6% vs 8%; p = 0.35) did not differ. Survival was lower in venoarterial extracorporeal membrane oxygenation (48%) than venovenous extracorporeal membrane oxygenation (64%) ( p < 0.001). After excluding studies that included extracorporeal cardiopulmonary resuscitation, no significant difference was seen in the rate of overall acute brain injury between venoarterial extracorporeal membrane oxygenation and venovenous extracorporeal membrane oxygenation (13% vs 10%; p = 0.4). However, ischemic stroke (10% vs 1%; p < 0.001), hypoxic-ischemic brain injury (7% vs 1%; p = 0.02), and brain death (9% vs 1%; p = 0.005) remained more frequent in nonextracorporeal cardiopulmonary resuscitation venoarterial extracorporeal membrane oxygenation compared with venovenous extracorporeal membrane oxygenation. Conclusions: Brain injury was more common in venoarterial extracorporeal membrane oxygenation compared with venovenous extracorporeal membrane oxygenation. While ischemic brain injury was more common in venoarterial extracorporeal membrane oxygenation patients, the rates of intracranial hemorrhage were similar between venoarterial extracorporeal membrane oxygenation and venovenous extracorporeal membrane oxygenation. Further research on mechanism, timing, and effective monitoring of acute brain injury and its management is necessary. Abstract : Supplemental Digital Content is available in the text.